Exploring Depression among Adolescents with Antisocial Behavioral Tendencies - Nur Hikma; Rizky Pradita Manafe; Zerlinda C. A. Sanam; Mardiana Artati; R. Pasifikus Christa Wijaya (Universitas Nusa Cendana, 2026)
Introduction Depression among adolescents with antisocial behavioral tendencies is often hidden behind observable behaviors such as rule-breaking, irritability, withdrawal, and interpersonal conflict. Aim This study aimed to explore how depression is experienced and expressed among adolescents with antisocial behavioral tendencies using a participatory Photovoice approach. Result Three interconnected themes emerged: adverse childhood experiences, antisocial coping, and depressive conditions. Family conflict, parental infidelity, bullying, academic pressure, and limited emotional support were associated with participants' negative perceptions of themselves, others, and their future. Antisocial behaviors were described not only as externalizing behaviors but also as maladaptive coping strategies used to manage unresolved emotional distress. Participants also described persistent sadness, loneliness, hopelessness, low self-worth, and social withdrawal as part of their depressive experiences. Conclusion These findings highlight the complex relationship between depression and antisocial behavioral tendencies and demonstrate the value of participatory approaches such as Photovoice in understanding adolescents' subjective emotional experiences.